Probiotic Treatment with a Gut Symbiont Leads to Parasite Susceptibility in Honey Bees. Issue 12 (December 2016) - Schmidt, Konstantin; Engel, Philipp
Abstract : Gut symbionts are critical for host health and as such might be used as probiotics. In a recent study, Schwarz et al. showed that pretreatment of honey bees with a dominant gut bacterium causes dysbiosis and increases pathogen susceptibility, showing that probiotic applications for animal health can have unwanted effects.